Synthesis and characterization of Zeolite/Fe3O4 nanocomposite by green quick precipitation method. - Jahangirian, Hossein; Ismail, Mohd Halim Shah; Haron, Md. Jelas; Rafiee-Moghaddam, Roshanak; Shameli, Kamyar; Hosseini, Soraya; Kalantari, Katayoon; Khandanlou, Roshanak; Gharibshahi, Elham; Soltaninejad, Sepideh (National Institute R and D of Materials Physics, 2013)
A green quick precipitation method was successfully used for synthesis of magnetic iron oxide nanoparticles (Fe3O4-NPs) on the surface of sodium/potassium type zeolite. Ferric chloride, ferrous chloride and sodium hydroxide aqueous solutions were used in the synthesis and coating of the Fe3O4-NPs on the surface of the zeolite to produce the zeolite/magnetic iron oxide nanocomposite (zeolite/Fe3O4 –NCs). The reaction was performed in aqueous suspension phase under the ambient condition as green chemistry method. Characterization with Fourier transforms infrared spectroscopy (FT‒IR), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), energy dispersive X-ray fluorescence (EDXF) and transmission electron microscopy (TEM) confirmed the formation of Fe3O4-NPs with mean particle sizes of 3.55±1.02 nm on the surface of the zeolite.